Correlation Between Increase of Axial Length and Height Growth in Chinese School-Age Children - Tao, Lixia; Wang, Chunxiao; Peng, Yiyi; Xu, Meiping; Wan, Minghui; Lou, Jiangtao; Yu, Xinping (Frontiers in Public Health, 2022)
Purpose: To identify the relationship between the increase in axial length (AL) and height in school-age children and explore the influence of refractive status on such a relationship. Methods: In this 5-year cohort study, 414 Chinese children (237 boys) aged 6–9 years (mean 7.12) underwent measurements annually. AL was measured using the Lenstar; height with the children standing, without shoes; and refraction using subjective refraction without cycloplegia. Participants were divided according to the refractive status: persistent emmetropia, persistent myopia, and newly developed myopia. The measurement time points of the persistent emmetropia and persistent myopia groups were marked as T1, T2, T3, T4, and T5. The time of myopia onset in the newly developed myopia group was marked as t0; the preceding time points were marked as t-1, t-2, and so on, and the succeeding as t1, t2, and so on. The association between increase in AL and height was analyzed using simple correlation analysis. Results: The mean changes in AL, height, and refraction were 1.39 mm, 23.60 cm, and −1.69 D, respectively, over 5 years in all children. The increase in AL and height were positively correlated for T1 T2, T1 T3, T1 T4, and T1 T5 (r=0.262, P<0.001; r=0.108, P=0.034; r=0.165, P=0.001; r=0.174, P=0.001, respectively). The changes in AL and height in the newly developed myopia group were significantly correlated (r=0.289, P=0.009) after myopia onset (t0 t2). Conclusion: The increase in AL and height were positively correlated, especially in the newly developed myopia group after myopia onset. Thus, when children grow quickly, AL elongation should be monitored.